Respuestas

2012-05-30T01:25:19+02:00



6x³+23x²+9x-18 = x³+23x/6+3x/2-3 = (x+a)(x+b)(x+c)

a, b, c deben dar -3 al multiplicarse. Probemos con

a=3
b=1
b=-1

(x+a)(x+b)(x+c) = (x+3)(x+1)(x-1) = (x²+4x+3)(x-1) =
x³+4x²+3x-x²-4x-3 = x³+3x²-x-3 ≠ x³+23x/6+3x/2-3

Probemos ahora con

a=3
b=3/2
c=-2/3

(x+a)(x+b)(x+c) = (x+3)(x+3/2)(x-2/3) = (x²+9x/2+9/2)(x-2/3) =
x³+9x²/2+9x/2-2x²/3-18x/6-18/6 = x³+23x²/6+9x/6-3 =
x³+23x²/6+3x/2-3

Por lo tanto:

6x³+23x²+9x-18 = x³+23x/6+3x/2-3 = (x+3)(x+3/2)(x-2/3)

Espero haber podido ayudarte. Saludos!

2012-05-30T06:48:53+02:00

6x³+23x²+9x-18 = x³+23x/6+3x/2-3 = (x+a)(x+b)(x+c)

a, b, c deben dar -3 al multiplicarse. Probemos con

a=3
b=1
b=-1

(x+a)(x+b)(x+c) = (x+3)(x+1)(x-1) = (x²+4x+3)(x-1) =
x³+4x²+3x-x²-4x-3 = x³+3x²-x-3 ≠ x³+23x/6+3x/2-3

Probemos ahora con

a=3
b=3/2
c=-2/3

(x+a)(x+b)(x+c) = (x+3)(x+3/2)(x-2/3) = (x²+9x/2+9/2)(x-2/3) =
x³+9x²/2+9x/2-2x²/3-18x/6-18/6 = x³+23x²/6+9x/6-3 =
x³+23x²/6+3x/2-3

Por lo tanto:

6x³+23x²+9x-18 = x³+23x/6+3x/2-3 = (x+3)(x+3/2)(x-2/3)